Improving how meteorological information is used by pastoralists through adequate communication tools. (October 2015) - Rasmussen, Laura Vang; Mertz, Ole; Rasmussen, Kjeld; Nieto, Hector
Abstract: In West Africa, the channels for information flow from meteorological services to end-users, such as pastoralists, are relatively limited. As meteorological information is key to improving productivity for pastoralists, it represents a challenge at both local and national level to develop an efficient information dissemination system. However, few studies have focused specifically on pastoralists as end-users, and the best mode of delivering meteorological information to pastoralists remains unknown. Drawing on fieldwork conducted in Burkina Faso using a combination of qualitative and quantitative methods, this paper examines 1) the principal modes used by pastoralists to receive information, and 2) in what form and by which type of media pastoralists actually prefer to receive information. It was found that mobile phones have replaced traditional forecasting methods as these were becoming unreliable with increased climate variability. The phone was used to acquire updated informal information on, for example, the arrival of the rain from friends and family staying in other areas. The findings illuminate how mobile phones have a huge potential to deliver more formal information to pastoralists, and we propose that forecasts should be available as voice messages in local languages rather than text messages. Highlights: Information on climate and weather is key to improving productivity for pastoralists. The formal information produced in West Africa is not received by pastoralists. Pastoralists prefer mobile phones for acquiring information from informal sources. The radio is not perceived a promising avenue for disseminating weather information. Forecasts should be issued as voice messages via mobile phones.